Pengaruh Metode PBL dalam Pembelajaran Menulis Teks Eksplanasi pada Siswa Kelas VIII SMP Negeri - Kamila, Devi Faricha Rahman; Susetyo, Agus Milu; Citraningrum, Dina Merdeka (Juwara: Jurnal Wawasan dan Aksara, 2024)
This study aims to analyze the impact of the problem-based learning method on Indonesian language learning for Grade VIII students at SMP Negeri 01 Mayang, particularly on explanatory text materials. The research employs a quantitative approach with an experimental method and a pretest-posttest control group design. The study involved 55 students divided into two classes as the control and experimental groups. Data were collected through pre-tests and post-tests to measure student performance before and after implementing the problem-based learning method. Data analysis was conducted using normality, homogeneity, and hypothesis tests with SPSS 18.0 for Windows. The results of the independent sample t-test indicated that the significance level (2-tailed) was higher than the predetermined alpha level, leading to the acceptance of the null hypothesis (Ho). The findings reveal that the problem-based learning method positively impacts improving students' understanding of explanatory text materials. This approach has proven effective in encouraging students to become more active, critical, and independent during the learning process. Therefore, this method is recommended as a teaching strategy to enhance the quality of Indonesian language learning at the junior high school level, particularly in explanatory text writing skills.